2011
DOI: 10.1071/ch11294
|View full text |Cite
|
Sign up to set email alerts
|

Borinic Acids: A Neglected Class of Organoboron Compounds for Recognition of Diols in Aqueous Solution

Abstract: Association constants between diphenylborinic acid and representative analytes capable of reversible two-point covalent binding (diols, catechols, and hydroxy acids) were determined using an indicator-displacement assay. Unlike boronic acids, which have been studied in great detail as receptors for diols and related compounds, borinic acids have effectively been ignored as candidates for such applications. The results of this study indicate that diphenylborinic acid displays high affinity for certain analytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…In galactopyranosides, there is an additional possible binding site: the C-3/C-4 cis-diol ( Figure 7): While a significant amount of research has been dedicated to the study of boronatemonosaccharide interactions, very little has been invested in borinate-monosaccharide exchange. Taylor has recently reported that borinic acids have substantial affinity for catechols and α-hydroxycarboxylates, [38] greater than that of 2-fluoro-5-nitrophenyboronic acid, [39] a boronate that is able to bind sugars at neutral pH. The affinity of this boronate for monosaccharides is greater than the affinity of a borinic acid for the same sugars, but this affinity in the latter case is still significant.…”
Section: Boron-based Monosaccharide Receptorsmentioning
confidence: 94%
“…In galactopyranosides, there is an additional possible binding site: the C-3/C-4 cis-diol ( Figure 7): While a significant amount of research has been dedicated to the study of boronatemonosaccharide interactions, very little has been invested in borinate-monosaccharide exchange. Taylor has recently reported that borinic acids have substantial affinity for catechols and α-hydroxycarboxylates, [38] greater than that of 2-fluoro-5-nitrophenyboronic acid, [39] a boronate that is able to bind sugars at neutral pH. The affinity of this boronate for monosaccharides is greater than the affinity of a borinic acid for the same sugars, but this affinity in the latter case is still significant.…”
Section: Boron-based Monosaccharide Receptorsmentioning
confidence: 94%
“…in catalysis[3436] and medicine[3741], although their utility in molecular recognition is only beginning to be exploited [35, 36, 4245]. Chudzinski et al [42] recently highlighted this “neglected class of organoboron compounds” for diol recognition and detailed the effectiveness of diphenylborinic acid to preferentially bind the diol compounds Catechol, L-Lactic Acid, and Alizarin Red S. Indeed, association constants for diphenylborinic acids bound to these particular substrates are nearly an order of magnitude larger than for similar boronic acids. Chudzinski et al [42] speculated that this increase in affinity towards Catechol, L-Lactic Acid, and Alizarin Red S could be a steric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Chudzinski et al [42] recently highlighted this “neglected class of organoboron compounds” for diol recognition and detailed the effectiveness of diphenylborinic acid to preferentially bind the diol compounds Catechol, L-Lactic Acid, and Alizarin Red S. Indeed, association constants for diphenylborinic acids bound to these particular substrates are nearly an order of magnitude larger than for similar boronic acids. Chudzinski et al [42] speculated that this increase in affinity towards Catechol, L-Lactic Acid, and Alizarin Red S could be a steric effect. However, there has been no systematic investigations of the structural and/or bonding differences in corresponding boronic and borinic acids that might help identify those features that affect their preference toward specific substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor describes the use of diarylborinic acids for diol and hydroxyacid receptors. [4] Fluorescent sensing of carbohydrates by boronic acids is a relatively young field less than two decades old [5] and targeting a-hydroxycarboxylates specifically with fluorescent boronates has only developed in the past decade. [6] However, little attention has been paid to borinic acids in these contexts.…”
mentioning
confidence: 99%
“…Taylor and co-workers have shown that borinic acids are particularly effective at binding to catechol-type systems. [4] Relative to analogous arylboronic acids, diarylborinic acids offer an additional handle for synthetic modification to tune the affinity and selectivity of boron-based receptors. Each aromatic group can be introduced sequentially offering an expanded number of potential analogues that can be accessed.…”
mentioning
confidence: 99%